(untitled) (Medico Legal Update, 2020)
Introduction: rosacea can diagnosis by presence permanent erythema of the arched sides of the face, cheeks and nose then it affect the chin as well as brow. Method: A cross sectional study design was implemented, 50 child of Rosacea, were collected from outpatients of dermatology and venereology in Merjan teaching hospital and Alhussein teaching hospital in Thi Qar, from Jan. 2018 to Jan. 2019. All patients were identified basing on the distinctive clinical features by dermatologist, and for suspicious cases biopsy was taken to confirm the diagnosis. Results: no significant association between age groups and gender of kids. Significant association between gender and types, 61.1% of females and 54% of males with with Erythemato telengectetic while 30% of females and 14% of males with mixed type. No significant association between gender and types of skin P-value more than 0.05. No significant association between gender and drugs used. P-value more than 0.05. Conclusion: There is significant association between female gender and Erythematotelengectetic and mix type of rosacea, while significant association between male gender and Papulopastular type of rosacea.